Implementation of Group Exchange Learning Model in The Subject Muthala’ah at Madrasah Aliyah Al-Umm Malang - Naufal Fikri; Muasshomah Muasshomah; Muhammad Safari; Shafrul Fajri (Universitas Ahmad Dahlan, 2023)
The aim of this study is to reveal the application of the learning model